Analysis of Risk Management on MSMEs (Case Study of The Bamboo Handicraft Industry) - Heni Hirawati; Yacobo P. Sijabat (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2020)
This article aims to identify the risks in the bamboo handicraft industry in Sendari, assessment of the risks that may arise and analyze the strategies. Risk identification in this study was carried out by conducting a SWOT analysis to determine the current business conditions and to analyze the sources of risk that this industry is likely to face. The analysis found that the most significant risks faced by the bamboo handicraft industry in Sendari are Market Risk and Operational Risk. The risk assessment matrix shows that market risk and operational risk are in the red zone, and the financial risk becomes the next focus because the financial risk is in the orange zone. The bamboo handicraft industry in Sendari needs to increase the marketing of its products and collaborate with the government to improve human resource management, financing, and product innovation.